Analisis Kebijakan Pemutusan Hubungan Diplomatik Oleh Aljazair Terhadap Maroko Tahun 2021 - Zulha, Michael Ahmad; Santoso, Made Panji Teguh; Gustianti, Nurbani Adine (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the policy of diplomatic severance undertaken by Algeria against Morocco in 2021. The research employs a qualitative approach with a descriptive method to understand the dynamics of the foreign policies of both countries. In this study, the prolonged conflict over the Western Sahara region is identified as the core of the tension between Algeria and Morocco, where both nations have conflicting national interests. The findings indicate that Algeria’s decision to cut diplomatic ties cannot be separated from historical and geopolitical factors, as well as various incidents that eroded mutual trust—such as allegations of espionage and provocative political statements. The severance of relations implies the failure of bilateral diplomacy and the intensification of regional rivalry.